2017
DOI: 10.1101/225250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paramecium Learning: New Insights and Modifications

Abstract: Learning is a fundamental process in neural systems. However, microorganisms without a nervous system have been shown to possess learning abilities. Specifically, Paramecium caudatum has been previously reported to be able to form associations between lighting conditions and cathodal shocks in its swimming medium. We have replicated previous reports on this phenomenon and tested the predictions of a molecular pathway hypothesis on paramecium learning. Our results indicated that in contrast to the previous repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…The results revealed that the paramecia in the experimental group spent more time near the side that had been paired with the cathode, either illuminated or dark, than the other groups. Alipour et al (2018) partially replicated the results of Armus et al (2006). They observed how paramecia linked high light intensities with cathodic shocks, but not dark stimulation.…”
Section: Learning In Protista: Parameciumsupporting
confidence: 64%
See 3 more Smart Citations
“…The results revealed that the paramecia in the experimental group spent more time near the side that had been paired with the cathode, either illuminated or dark, than the other groups. Alipour et al (2018) partially replicated the results of Armus et al (2006). They observed how paramecia linked high light intensities with cathodic shocks, but not dark stimulation.…”
Section: Learning In Protista: Parameciumsupporting
confidence: 64%
“…From the early studies by Jennings (1904, 1906) to the most recent ones (Alipour et al, 2018), the same pattern can be detected about learning research in this eukaryote. The early work suggested that learning in paramecia had occurred, but subsequent authors questioned the results by arguing the lack of control for several variables.…”
Section: Learning In Protista: Parameciumsupporting
confidence: 54%
See 2 more Smart Citations
“…Thus, after training, Paramecium spends more time than before in the lighted compartment. This interpretation is supported by the observation that the "trained" behavior only occurs when the cathodal compartment is lighted during training (Alipour et al, 2018), and by the absence of retention (Mingee, 2013).…”
Section: Learningmentioning
confidence: 82%